2014
DOI: 10.1179/0001551214z.00000000035
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence in a cohort of Belgian HIV patients: a pilot study

Abstract: Since the era of highly active antiretroviral therapy (HAART), HIV is considered a chronic disease. Adherence to HAART is crucial for effectiveness. Non-adherence negatively impacts patient outcome and the larger economy. However, data on adherence among the Belgian HIV cohort are scarce. Therefore, the purpose of this pilot study was to identify determinants of adherence among HIV patients treated in Belgium. The study was conducted at the Aids Reference Centre of Ghent University Hospital between 1 January a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 28 publications
2
13
0
9
Order By: Relevance
“…Fisher's Exact Test and Pearson's Chi-Square were then used to verify the association of NDs, which had a frequency of over 50% in people living with AIDS, with the following sociodemographic and clinical characteristics: age, gender, marital status, family income, modes of transmission of HIV, existence of other diseases, current opportunistic infection, abandonment of treatment, difficulty in accessing to service, being smoker, alcohol consumer and drug user. The characteristics frequently studied in research involving people living with AIDS (9)(10)(11)(12)(13)(14)(15) were used. There was a significance level of 5%.…”
Section: Analysis Of Results and Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fisher's Exact Test and Pearson's Chi-Square were then used to verify the association of NDs, which had a frequency of over 50% in people living with AIDS, with the following sociodemographic and clinical characteristics: age, gender, marital status, family income, modes of transmission of HIV, existence of other diseases, current opportunistic infection, abandonment of treatment, difficulty in accessing to service, being smoker, alcohol consumer and drug user. The characteristics frequently studied in research involving people living with AIDS (9)(10)(11)(12)(13)(14)(15) were used. There was a significance level of 5%.…”
Section: Analysis Of Results and Statisticsmentioning
confidence: 99%
“…The use of alcohol and other drugs are among the main factors leading to abandonment of treatment. However, researchers in Belgium identified that 78.55 to 93.5% of the survey participants were smokers, who reported that alcohol and tobacco were not grounds for dropping out of treatment, but were interpersonal conflicts, and the stigma of the disease (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be avoided by providing necessary knowledge of how to live with HIV/AIDS. Encouragement and providing social support through community worker can alleviate the depression problem and finally improve adherence [36]. Antidepressants medications are also used in most studies to alleviate the depression and this treatment has increased the adherence to HAART [37][38][39].…”
Section: Aupc=881%mentioning
confidence: 99%
“…En la descripción de las características demográficas de los participantes, se observa una mayor proporción de hombres. Considerando que hay más depresión en mujeres que en hombres 8 , podríamos inferir que hay una subestimación de la medida de asociación. Asimismo, los modelos de regresión no consideran todos los confusores que se leen en la literatura especializada, lo cual hace difícil al lector saber si el efecto realmente es el mostrado.…”
unclassified